2004
DOI: 10.1097/00004872-200401000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide prevalence of hypertension

Abstract: Hypertension is an important public health challenge in both economically developing and developed countries. Significant numbers of individuals with hypertension are unaware of their condition and, among those with diagnosed hypertension, treatment is frequently inadequate. Measures are required at a population level to prevent the development of hypertension and to improve awareness, treatment and control of hypertension in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
703
6
83

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,020 publications
(823 citation statements)
references
References 51 publications
31
703
6
83
Order By: Relevance
“…Hypertension (as well as diabetes and dyslipidemia) is a major problem in Asia Pacific regions, including China, and high blood pressure is poorly controlled (12,13). In a study conducted in Leicestershire, United Kingdom (14), involving 5789 consecutive patients admitted with HF, admission rates for HF were higher among South Asian patients than white patients.…”
Section: The South Asian Populationmentioning
confidence: 99%
“…Hypertension (as well as diabetes and dyslipidemia) is a major problem in Asia Pacific regions, including China, and high blood pressure is poorly controlled (12,13). In a study conducted in Leicestershire, United Kingdom (14), involving 5789 consecutive patients admitted with HF, admission rates for HF were higher among South Asian patients than white patients.…”
Section: The South Asian Populationmentioning
confidence: 99%
“…1,2 This condition is directly related to the development of cardiovascular diseases, encephalic vascular accident and renal insufficiency. 3 The risk factors for hypertension are associated with many other factors, including lifestyle.…”
Section: Introductionmentioning
confidence: 99%
“…Further research should focusIntroduction Most European studies have consistently shown lower blood pressure (BP) levels in women than in men. [1][2][3][4] This sex difference in BP in populations of European descent appears during adolescence and persists up to the age of 60 years. 3,5 The mechanisms underlying the sex difference in BP are not well understood, but sex hormones have been suggested as a possible cause.…”
mentioning
confidence: 99%